Islamic Worldview as a Basis for Islamization of Science Concept According to Syed Muhammad Naquib Al-Attas - Al Haidary, Abdullah Haq; Al Faruqi, Achmad Reza Hutama; Shofwan MF, Abbas; Maafi, Rif'at Husnul (KALAM, 2024)
This article identifies the crisis of Muslim identity in science, caused by the blind adoption of Western secular science that separates spiritual values from knowledge, contrary to the Islamic concept of tawḥīdi. The researcher highlights the urgency of Syed Muhammad Naquib Al-Attas' Islamization of science in integrating spiritual values in science and overcoming the dominance of Western secular thought that threatens Islamic identity and theology. For this research to run according to its purpose, researchers use analytical methods to analyze current problems in science and religion. The result was that Syed Muhammad Naquib al-Attas emphasized the establishment of an Islamic epistemological framework through the basis of the Islamic Worldview. Islamization is a response to the negative impact of Western science on society, by offering an Islamic worldview as the basis for Muslim life.